1H-MRS neurometabolite profiles and motor development in school-aged children who are HIV-exposed uninfected: a birth cohort study - Williams, Simone R.; Robertson, Frances C.; Wedderburn, Catherine J.; Ringshaw, Jessica E.; Bradford, Layla; Nyakonda, Charmaine N.; Hoffman, Nadia; Joshi, Shantanu H.; Zar, Heather J.; Stein, Dan J.; Donald, Kirsten A. (Frontiers in Neuroscience, 2023)
Objective Alterations in regional neurometabolite levels as well as impaired neurodevelopmental outcomes have previously been observed in children who are HIV-exposed uninfected (CHEU). However, little is known about how neurometabolite profiles may relate to their developmental impairment. This study aimed to compare neurometabolite concentrations in school-aged CHEU and children who are HIV-unexposed (CHU) and to explore associations of neurometabolite profiles with functional neurodevelopment in the context of perinatal HIV exposure. Methods We used 3 T single voxel proton magnetic resonance spectroscopy (1H-MRS) to quantify absolute and relative neurometabolites in the parietal gray and parietal white matter in school-aged CHEU and aged- and community-matched CHU. Functional neurodevelopmental outcomes were assessed using the early learning outcome measure (ELOM) tool at 6 years of age. Results Our study included 152 school-aged children (50% males), 110 CHEU and 42 CHU, with an average age of 74 months at the neuroimaging visit. In an adjusted multiple linear regression analysis, significantly lower glutamate (Glu) concentrations were found in CHEU as compared to CHU in the parietal gray matter (absolute Glu, p = 0.046; Glu/total creatine (Cr+PCr) ratios, p = 0.035) and lower total choline to creatine ratios (GPC+PCh/Cr+PCr) in the parietal white matter (p = 0.039). Using factor analysis and adjusted logistic regression analysis, a parietal gray matter Glu and myo-inositol (Ins) dominated factor was associated with HIV exposure status in both unadjusted (OR 0.55, 95% CI 0.17–0.45, p = 0.013) and adjusted analyses (OR 0.59, 95% CI 0.35–0.94, p = 0.031). With Ins as one of the dominating metabolites, this neurometabolic factor was similar to that found at the age of two years. Furthermore, this factor was also found to be correlated with ELOM scores of gross motor development in CHEU (Pearson’s r = −0.48, p = 0.044). In addition, in CHEU, there was a significant association between Ins/Cr+PCr ratios in the parietal white matter and ELOM scores of fine motor coordination and visual motor integration in CHEU (Pearson’s r = 0.51, p = 0.032). Conclusion Reduced Glu concentrations in the parietal gray matter may suggest regional alterations in excitatory glutamatergic transmission pathways in the context of perinatal HIV and/or antiretroviral therapy (ART) exposure, while reduced Cho ratios in the parietal white matter suggest regional myelin loss. Identified associations between neurometabolite profiles and gross and fine motor developmental outcomes in CHEU are suggestive of a neurometabolic mechanism that may underlie impaired motor neurodevelopmental outcomes observed in CHEU.